Faufil et petit point Une analyse montagnaise de la locomotion - Savard, Rémi (Anthropologica, 2022)
A certain reading of one episode of the narrative cycle of the Trickster points out the treatment given by the Montagnais tradition to the phenomenon of animal locomotion. It is integrated in a typically algonquin cosmological cycle.